The Influence of Leadership, Organizational Culture, Work Motivation and Rewards on the Performance of Elementary School Certified Teachers - Bangun, Esdras Silverius; Lian, Bukman; Mahasir, Mahasir (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This study aims to determine and describe the influence of leadership, organizational culture, motivation and reward on the performance of certified elementary school teachers in Central Bangka Regency. This study was conducted on elementary school certified teachers in Central Bangka Regency. This research is descriptive quantitative. The samples in this study were 399 teachers. The data analysis technique used is a multiple regression model with the help of the SPSS for Windows program. The results of the study concluded that there was a significant influence between leadership, organizational culture, work motivation and reward on the performance of certified elementary school teachers in Central Bangka Regency.